Efficacy of direct anterior approach combined with direct posterior approach in Pipkin IV femoral head fractures - Bo Liu; Binghao Zhao; Qingsong Zhang (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Objective The study aimed to explore the efficacy of direct anterior approach combined with direct posterior approach in Pipkin IV femoral head fractures. Methods The study enrolled 64 patients with Pipkin IV femoral head fractures who were treated at our hospital between March 2019 and April 2020. They were assigned to the control group and the study group using the random number table method with 32 patients in each group and received treatment by the direct anterior approach and treatment by the direct anterior approach combined with the direct posterior approach. The operative time, intraoperative estimated blood loss, postoperative drainage time, drainage volume, time to partial and full weight-bearing, total length of hospital stay and the levels of hemoglobin (Hb) and hematocrit (Hct) in the two groups were compared, and severity of pain and hip function at different time points postoperatively were observed, and the occurrences of complications were compared. Results There was no statistical difference in the operative time and intraoperative estimated blood loss between the two groups (P > 0.05). Compared with the control group, the study group had shorter postoperative drainage time, lower drainage volume, shorter time to partial and full weight-bearing, and shorter total length of hospital stay, and the difference was statistically different (P < 0.05). There was no significant difference in Hb and Hct levels between the two groups before surgery (P > 0.05). The levels of Hb and Hct in both groups at postoperative day (POD) 1 were lower than those before surgery, and the levels of Hb and Hct in the study group were significantly higher than those in the control group (P < 0.05). Compared with the control group, the study group had significantly less severe pain at POD 1 and 7 and 1, 3 and 6 months postoperatively (P < 0.05). Compared with the control group, the study group had significantly better hip function at 3, 6 and 12 months postoperatively (P < 0.05). All patients were followed up for 12 months, and 1 case of ectopic ossification appeared in both groups 3 months postoperatively, both Brooker grade I. No special treatment was provided as it did not interfere with the mobility of the hip and caused no apparent discomfort in the patients. In the current study, no incision infection, ischemic necrosis of the femoral head, breakage of the internal fixation device, fracture nonunion and loss of fracture reduction and other complications were reported in any patients. Conclusion Direct anterior approach combined with direct posterior approach in Pipkin IV femoral head fractures does not increase operative time and intraoperative estimated blood loss but can lessen severity of pain and promote functional recovery of the hip, leading to a favorable prognosis while not increasing the incidence of complications.